Liver transplantation and COVID-19: a case report and cross comparison between two identical twins with COVID-19 - Hamed Nikoupour (BMC Surgery, 2020)
Abstract Background To this date little information exists on the effects, clinical course and outcome of the COVID-19 among patients undergoing transplantation. Case presentation A 35 year old male referred with loss of sense of smell and taste after having close contact with his brother who was diagnosed with COVID-19 five days prior to his symptoms. The patient had undergone liver transplantation 3 years prior to his referral due to primary sclerosing cholangitis in association with ulcerative colitis and was using immunosuppressive medications. The patient referred to a local physician with mild symptoms of fatigue, cough, myalgia, dizziness, and nausea/vomiting with a fear of contracting the disease. Except for a CRP of 32 his other blood tests were normal. After 3 days of hospital admission the patient was discharged with a good condition. His brother had developed fever, chills, headache, mild dyspnea and an objective loss of sense of smell and taste and was sent home and advised to self-quarantine. Both patients had CT scans in favor of COVID-19. Conclusion Our patient who had liver transplantation and COVID-19 did not present more severe symptoms compared to his counterpart without liver transplantation and did not need to be hospitalized or be given antiviral drugs for COVID-19.